The Role Of Collaborative Governance As An Effort To Activate Creative Centres: A Phenomenological Study In Purwakarta - Putritirano, Shaqina Zahra; Novarlia, Irena; Supriyadi, Tedi (UNIVERSITAS PAKUAN, 2025)
The implementation of collaborative governance in managing the creative economy sector has become increasingly essential, particularly at the local level where multiple stakeholders interact. This study explores the role of collaborative government in the activation process of the Creative Center Purwakarta (CCP), a collaborative space established to support creative community activities in Purwakarta, West Java. Employing a qualitative phenomenological approach, the research involved ten key informants, including government officials, CCP managers, members of creative communities, and residents directly engaged in the use of CCP. Data collection was conducted through in-depth interviews and document analysis. The findings reveal that although the government has provided facilities and regulatory support, collaboration remains limited to administrative coordination and has yet to fully foster participatory and innovative synergy. Personal engagement strategies, the government's facilitative role, and the ability to adapt to policy changes emerged as key factors driving effective collaboration. The study concludes that the successful activation of CCP requires a dialogic collaborative structure, facilitative leadership, and governance that is responsive to local policy dynamics. These findings offer practical implications for local governments in strengthening creative ecosystems and contribute to the theoretical development of collaborative governance in the creative economy sector.